Wybrane rodzaje składek w modelu ryzyka kolektywnego - Nowicka-Zagrajek, Joanna; Burnecki, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this paper we present the most important premium calculation principles for the collective risk model, namely equivalence, expected value, variance, standard deviation and exponential principles. Moreover, we study premiums for normal and translated gamma approximations. We illustrate theoretical results on a real-world natural catastrophe loss data. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 48-55